Behavioral Medicine and Integrated Care Efficient Delivery of Effective Treatments (Springer International Publishing, 2018)
This evidence-to-practice volume deftly analyzes the processes and skills of integrating mental healthcare with primary care, using multiple perspectives to address challenges that often derail these joint efforts. Experts across integrative medicine offer accessible blueprints for smoothly implementing data-based behavioral interventions, from disease management strategies to treatment of psychological problems, into patient-centered, cost-effective integrated care. Coverage highlights training and technology issues, key healthcare constructs that often get lost in translation, and other knowledge necessary to create systems that are rooted in-and contribute to-a robust evidence base. Contributors also provide step-by-step guidelines for integrating behavioral health care delivery in treating cancer, dementia, and chronic pain. Among the topics covered: The epidemiology of medical diseases and associated behavioral risk factors. Provider training: recognizing the relevance of behavioral medicine and the importance of behavioral health consultations and referrals. Screening for behavioral health problems in adult primary care. Health care transformation: the electronic health record. Meeting the care needs of patients with multiple medical conditions. Smoking cessation in the context of integrated care. This depth of clinical guidance makes Behavioral Medicine and Integrated Care an essential reference for practitioners on all sides of the equation, including health psychologists and other professionals in health promotion, disease prevention, psychotherapy and counseling, and primary care medicine.